Optimalkan Pemasaran Pande Besi Dengan Whatsapp Business dan Katalog di Desa Sumberpasir Kabupaten Malang: Optimize Pande Besi Marketing With Whatsapp Business and Catalog in Sumberpasir Village, Malang Regency - Basid, Abdul; Amanda Eka Putri, Nur Faizin, Hasyyati Labibah, Herdyawan Natahadi, (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This article aims to optimize the marketing of products and services in Sumberpasir Village through the use of WhatsApp Business and Catalog. This research reveals the functions and benefits of WhatsApp Business in marketing, identifies the profile of Sumberpasir Village as a marketing potential, and explains the role of WhatsApp Business in supporting marketing efforts in the village. WhatsApp Business is a communication platform that allows businesses to interact directly with customers. Its main function is to strengthen the connection between customers and businesses, facilitate two-way communication, as well as provide tools to efficiently manage messages. This article highlights the benefits of WhatsApp Business in marketing, such as increasing customer engagement rates, expanding marketing reach, and increasing customer trust in businesses. Sumberpasir Village has great marketing potential, especially in local products and tourism. The profile of Sumberpasir Village as a unique rural area and rich in local culture is the main attraction for marketing. This article discusses the potential of Sumberpasir Village's superior products that can be promoted through WhatsApp Business and Catalog to attract customers from outside the village. The use of WhatsApp Business in villages opens up opportunities for micro and small businesses to develop and increase competitiveness in local and regional markets. The results of this service show that WhatsApp Business and Catalog have an important role in optimizing marketing in Sumberpasir Village.